Roxane Gay’s Hunger: A Memoir of (My) Body: A Fat Studies Approach - Md Tapu Rayhan; Nure Jannat; Maruf Rahman (European Scientific Journal, ESJ, 2020)
There is much scholarly research about the impact of popular culture messages regarding fatness on people, but there is limited study on people’s attitudes to those fat-shaming messages. Roxane Gay’s Hunger: A Memoir of (My) Body is a memoir of her own body, traumatic journey, and fatness. This article looks through this memoir to find out Roxane Gay’s attitude towards these messages in showing how people accept, react, and subvert these messages. This study will present this memoir as a manifestation of the prevailing negative representations of fat people in popular culture and how Gay, before and after being fat, responds to those fat-shaming messages produced by popular culture. This article, under the umbrella of Fat Studies, will discuss how Gay, because of her fatness, has been treated as other and marginalized in popular culture and how she presents herself as a proponent of Fat Studies. This research, discussing Gay's attitude to popular culture messages regarding fatness, willshow how Gay, through this memoir, protests against fat-shaming messages and how she becomes the voice of every fat person.